HUBUNGAN ANTARA KONSEP PERAN GENDER TERHADAP MINAT BELAJAR BIDANG TATA BOGA SISWA LAKI-LAKI KELAS X DI SMK SAHID SURAKARTA - Carissia, Astri (Universitas Sahid Surakarta, 2013)
The concept of gender roles in adolescent affects in their motivation learning especially in the culinary sector. It is based on the observation in tourism schools. The most students who are continuing their education in the culinary sector are women. The population of the study is 84 male students of class X SMK Sahid Surakarta. Meanwhile, sample is not used in this study. This is because it use to minimize errors and generalization of the results from the research. Pearson product moment analysis that is used to examine the correlation of variable concepts from gender roles and culinary learning motivation shows = 0458 with p-value 0.000 <0.01. The conclusion of this study is there is a significant correlation between concept of gender roles with learning motivation of the culinary sector from male students of class X at SMK Sahid Surakarta. The contribution is 45.80% from the concept of gender roles in learning motivation of culinary.